2017
DOI: 10.1038/s41598-017-14646-9
|View full text |Cite
|
Sign up to set email alerts
|

The food-borne pathogen Campylobacter jejuni depends on the AddAB DNA repair system to defend against bile in the intestinal environment

Abstract: Accurate repair of DNA damage is crucial to ensure genome stability and cell survival of all organisms. Bile functions as a defensive barrier against intestinal colonization by pathogenic microbes. Campylobacter jejuni, a leading bacterial cause of foodborne illness, possess strategies to mitigate the toxic components of bile. We recently found that growth of C. jejuni in medium with deoxycholate, a component of bile, caused DNA damage consistent with the exposure to reactive oxygen species. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Inhibitors of RexAB would be expected to enhance the bactericidal activity of several different classes of antibiotic, as well as reduce the induction of the mutagenic SOS response, which is associated with the emergence of antibiotic resistance and mutants that can resist host immune defences [52,53]. We have also recently shown that DNA DSB repair is important for staphylococcal resistance to host immune defences, in keeping with similar findings with several other bacterial pathogens, providing an additional potential benefit of targeting this complex [34,54,55,56,57].…”
Section: Discussionsupporting
confidence: 61%
“…Inhibitors of RexAB would be expected to enhance the bactericidal activity of several different classes of antibiotic, as well as reduce the induction of the mutagenic SOS response, which is associated with the emergence of antibiotic resistance and mutants that can resist host immune defences [52,53]. We have also recently shown that DNA DSB repair is important for staphylococcal resistance to host immune defences, in keeping with similar findings with several other bacterial pathogens, providing an additional potential benefit of targeting this complex [34,54,55,56,57].…”
Section: Discussionsupporting
confidence: 61%
“…Previous work demonstrated the requirement of DNA DSB repair for the survival of Gram-negative pathogens in vivo . For example, AddAB was shown to be required for the infection of chickens and mice by Campylobacter jejuni and Helicobacter pylori , respectively ( 44 , 45 ). Furthermore, the virulence of Salmonella enterica in a murine model of bacteremia was dependent upon the RecBCD DNA DSB repair complex ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated the requirement of DNA DSB repair for the survival of Gram-negative pathogens in vivo . For example, AddAB was shown to be required for the infection of chickens and mice by Campylobacter jejuni and Helicobacter pylori respectively 41,42 . Furthermore, the virulence of Salmonella enterica in a murine model of bacteraemia was dependent upon the RecBCD DNA DSB repair complex 43 .…”
Section: Discussionmentioning
confidence: 99%